Peran Media Internet dan Perilaku Terhadap Efektivitas Belajar Mahasiswa Universitas Batanghari (Unbari) di Masa Pandemi Covid-19 - Fakhrul Rozi Yamali; Venny Yusiana; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this study is to find out and analyze whether there is a role for internet media and together or individually on the teaching effectiveness of Unbari students during the covid-19 pandemic. This reseach focuses on bathches of Unbari student respondents who are active in 2019 and 2020. The method in this research is qualitative with observational analytical methods through the distribution of questionnaires. The framework in this study is based on a cross-sectional study approach with a minimum sample spread for 3 variables as many as 323 respondents. Based on the results of the hypothesis, it is suspected that internet media and behavior together or alone play a role in the learning effectiveness of Unbari students. The results of data analysis based on univariate analysis stated that 50.8% of respondents stated that online learning was not effective and based on bivariate analysis of internet media and behavior had a significant role on learning effectiveness. Simultaneously, the role of internet media and behavior on the effectiveness of Unbari student learning during the covid-19 pandemic with an F value of 54,526.